The Development of Reading Comprehension Ability of Pratomsuksa 3 Students using SQ4R Integrated with Mind Mapping Learning Management - Warawan Nansathit; Autthapon Inthasena (Journal of Humanities and Social Sciences Mahasarakham University, 2022)
The purposes of the study were. -1) to develop an SQ4R integrated with mind mapping learning management with an efficiency of 75/75 for Pratomsuksa 3 students, 2) to study reading comprehension ability of students learning with developed learning management, and 3) to study students’ satisfaction toward learning management SQ4R integrated with mind mapping. the sample study group was selected by the purposive sampling method. The samples were 8 Pratomsuksa 3 students in Khummun Phadungwit School under control of Kalasin Primary Education Service Area 2 in the second semester of the 2020 academic year. The research instruments were. - 1) an SQ4R integrated with mind mapping learning management plans which consisted of 6 sub learning plans under 12 learning hours, 2) a reading comprehension test designed to have 20 items of 3 multiple choices and proven to have difficulty of 0.63-0.75, discrimination of 0.25-0.75, and reliability of 0.94, and 3) a satisfaction questionnaire designed to have 10 question items with discrimination of 0.52-0.91 and reliability of 0.9. The statistics used in data analysis were percentage, mean score, standard deviatin, and a nonparametrict test, the Wilcoxon Signed Rank test. The results of the study were as follows. 1.The SQ4R integrated with mind mapping learning management plans for Pratomsuksa 3 students was found to have efficiency at 79.88/80.83 reaching the criteria of 75/75 2. Students’ reading comprehension ability was significantly higher after learning with SQ4R integrated with mind mapping learning management plans at a statistical level of.05 3. The students’ satisfaction toward learning management SQ4R integrated with mind mapping was found at a very high ( =4.73, S.D.=0.35)